Zinc toxicosis — Associated hemolytic anemia and pancreatic disease in 2 dogs - Foote, Kimberley (Can Vet J, 2020)
Two cases of canine zinc toxicosis with pancreatic disease are reported. Both dogs had pigmenturia, pallor, regenerative anemia, an inflammatory leukogram, hyperbilirubinemia, hyperamylasemia, and hyperlipasemia. Zinc toxicosis was diagnosed post-mortem in patient 1 based on the discovery of a metallic gastric foreign object, pancreatic necrosis, nephrosis, and high tissue zinc concentrations. Survey radiographs of patient 2 allowed identification and prompt removal of coins from the stomach with resolution of anemia, hyperamylasemia, and hyperlipasemia 3 days post-gastroscopy. Plasma zinc concentration was markedly elevated in patient 2. Zinc toxicosis should be considered in dogs with concurrent hemolytic anemia and pancreatic disease.